Lithofacies Architecture and Distribution Patterns of Lacustrine Mixed Fine-Grained Rocks —a Case Study of Permian Lucaogou Formation in Jimsar Sag, NW China - Yin, Senlin; Zhu, Baiyu; Wu, Youxin; Xu, Feng (Frontiers in Earth Science, 2021)
As the controlling effect of complex lithofacies of lacustrine mixed fine-grained rocks on shale oil sweet-spot remained unclear, the core, outcrop, general logging, nuclear magnetic resonance (NMR) logging, testing and production data were used to study the types, combination pattern and genesis of lithofacies architectures of the lacustrine mixed fine-grained rocks in the study area by lithofacies hierarchy analysis, X-ray fluorescence (XRF) logging, UAV and 3D geological modeling. The research shows that: (1) According to lithology and sedimentary structure, the mixed fine-grained rocks can be divided into 13 lithofacies types of different origins in 5 sub-categories and 2 categories. (2) UAV photography was combined with traditional field survey to characterize the 3D spatial distribution of lithofacies architecture of the Lucaogou Formation on the outcrop, and it is found that the lithofacies architecture patterns of mixed fine-grained rocks include three types: gradual change type, abrupt change type and special type. The gradual change type with higher sand development degree and symmetrical lithofacies architecture has high quality reservoir with dissolution pores, and is mixed beach-bar sand in mixed zone. It is high in development degree and often appears as several similar cycles stacking over each other. The abrupt change type can be subdivided into two sub-types, asymmetric, and smaller in reservoir thickness. It is very high in development degree and often comes in several similar cycles. The special type belongs to thick clastic rock relatively independent in the mixed fine-grained rocks with a high development degree of sand. The sand is higher quality reservoir with properties of tight reservoir. It often appears as stacking of single cycle sand. (3) The different lithofacies architectures in the mixed fine-grained rocks have significant differences in distribution. The gradual change type is mainly composed of mudstone, dolomitic siltstone, sandy dolomite, dolomitic siltstone and mudstone, and appears in lenticular shape overlapping with each other on the plane. The abrupt change type is made up of felsic siltstone, dolomitic siltstone, sandy dolomite and mudstone, and appears as isolated thin layers on the plane. The special type is mainly composed of mudstone, felsic siltstone, and mudstone.